Effect of Providing Ostomy Care Education to Mothers of Neonates with Peristomal Skin Complications - Robatmili, Azar; zohari anboohi, sima; shirin abady farahani, azam; Nasiri, Malihe (Advances in Nursing & Midwifery, 2018)
Abstract Introduction: Ostomy is a surgical procedure performed to divert feces and urine output in cases of anorectal anomalies. Although this procedure is a crucial intervention with excellent treatment effect, it is associated with complications, such peristomal skin lesions. This study aimed at evaluating the effect of providing ostomy care education to mothers of infants with peristomal skin complications. Methods: Forty mothers of neonates with intestinal stomies were informed about the aim of this study and invited to participate. The sampling was conducted in accordance with the quota sampling method. The participants were randomly and equally allocated to the control and experimental groups. The mothers in the experimental group attended a three-session educational program, whereas the mothers in the control group received information about routine care methods used by the study settings. The peristomal skin conditions of the infants in both groups were examined before discharge and 30 days after discharge using the Telegram Software or in person, according to an established checklist. Data were analyzed with the SPSS 21 software to obtain descriptive and analytical statistics. Results: Prior to discharge, the majority of the neonates in both groups had healthy peristomal skin. In the control group, five neonates had acute dermatitis and one had chronic dermatitis. In the experimental group, four neonates had acute dermatitis and two had chronic dermatitis. The χ-square test showed that the two groups were not significantly different (p-value = 0.94). After discharge, most of the neonates in the experimental group had intact peristomal skin and only four neonates had chronic dermatitis. In contrast, in the control group, only six neonates had intact peristomal skin. The results of Fisher’s exact test indicated that the two groups of study were significantly different (p-value = 0.013). In the experimental group, 16 and 14 neonates had intact peristomal skin before and after discharge, respectively. In the control group, 14 and 6 neonates had intact peristomal skin before and after discharge, respectively. The results of McNemar’s test revealed no significant differences in the experimental group before and after discharge (p-value = 0.69), whereas the control group showed significant difference in this context (p-value = 0.021). Conclusions: Providing mothers with education on proper ostomy care significantly decreased the occurrence of peristomal skin lesions in neonates with intestinal ostomies.